POTENTIAL OF ORGANIC AGRICULTURE DEVELOPMENT - Ansabayeva, А. S.; Bolotov, V. S. (Ғылым және білім №1, 2020)
The article presents comparative results of introduction of organic agriculture in the world and the Republic of Kazakhstan on the example of Kostanay region. Organic agriculture aims to build production systems that improve and maintain soils that focus on improving human health, preserving ecosystems, while using innovation and scientific advances to benefit the environment. The introduction of organic agriculture will involve all actors in rural areas and not only, but the organic system is based on environmental processes that have no adverse effects and take into account local climatic conditions. Organic farming, as a factor of sustainable development, will result in the creation of ecological products (bio-products, organic products), a category of goods that are produced according to all necessary standards and are oriented to the human and environment. In the world, 172 countries are engaged in and developing organic farming, ensuring the sustainable development of their territories and economies, and investing in organic production, these countries are developing human potential. In Kostanay region large enterprises engaged in production of organic products are mainly farms from Fedorovsky district: LLP «Zharkol 007», LLP «Galant», LLP «Quarta», LLP «Bekseites», LLP «Metelica», LLP «Kovrizhny» are engaged in the production and processing industries. В статье приведены сравнительные результаты внедрения органического сельского хозяйства в мире и Республике Казахстан на примере Костанайской области. Органическое сельское хозяйство направлено на формирование систем производства, которое улучшает и поддерживает состояние почв, ориентированное на повышение здоровья людей, сохранение экосистем, при этом используя инновации и научные достижения с пользой для окружающей среды. При внедрении органического сельского хозяйства в этот процесс будут вовлечены все субъекты сельской местности и не только, данная органическая система берет за основу экологические процессы, которые не имеют пагубных последствий и учитывают местные климатические условия. Результатом органического земледелия, как одного из факторов устойчивого развития, будет создание экологических продуктов (биопродукты, органическая продукция), категория товаров, которые производятся с учетом всех необходимых норм и ориентированы на человека и окружающую среду.
Keywords: земледелие; органическое сельское хозяйство; organic agriculture; sustainable development; environmental products; рк